2019
DOI: 10.1007/s10562-019-03051-8
|View full text |Cite
|
Sign up to set email alerts
|

Ni–Zn–Al-Based Oxide/Spinel Nanostructures for High Performance, Methane-Selective CO2 Hydrogenation Reactions

Abstract: In the present study, NiO modified ZnAl 2 O 4 and ZnO modified NiAl 2 O 4 spinel along with pure Al 2 O 3 , ZnAl 2 O 4 and NiAl 2 O 4 for comparison in the CO 2 hydrogenation reaction have been investigated. It was found that NiAl 2 O 4 , NiO/ZnAl 2 O 4 and ZnO/NiAl 2 O 4 catalysts exhibited outstanding activity and selectivity towards methane even at high temperature compared to similar spinel structures reported in the literature. NiO/ZnAl 2 O 4 catalyst showed CO 2 consumption rate of ~ 19 μmol/g·s at 600 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…and ZnAl2O4 supports, respectively, or a possible overlap with the supports' diffraction peaks [41].…”
Section: Sem Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…and ZnAl2O4 supports, respectively, or a possible overlap with the supports' diffraction peaks [41].…”
Section: Sem Analysismentioning
confidence: 99%
“…This indicated that spinel in obtained nanocomposites was non-stoichiometric.When the reaction temperature was increasing, the diffraction peaks of the samples were slightly expanded (Figure4). For NiAl 2 O 4 and ZnAl 2 O 4 samples, no peak characteristics of NiO and ZnO were seen, indicating the fine dispersion of these species on the NiAl 2 O 4 and ZnAl 2 O 4 supports, respectively, or a possible overlap with the supports' diffraction peaks[41].…”
mentioning
confidence: 97%
“…The strong interaction between Ni and spinel oxide supports could improve the dispersion of Ni particles and thus construct more metal−support interfaces. Park et al 125 developed MgAl 2 O 4 -and MnAl 2 O 4 -supported Ni catalysts, where Ni functioned as the H 2 dissociation site. The outstanding performance of methanation was due to the enhanced synergic effect of moderate basic sites and well-dispersed metallic Ni.…”
Section: Introductionmentioning
confidence: 99%
“… 11 13 The proper combination of reducible oxides with nonprecious metals or spinel structures can also lead to CH 4 formation during the CO 2 hydrogenation. 14 , 15 In the synthesis of methanol, mainly Cu and Cu-Zn oxide based catalysts are employed. 16 Producing long-chain hydrocarbons is also in the focus of research, typically employing tandem catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…supported on semiconducting oxides (TiO 2 , CeO 2 , etc.) at ambient pressures. The proper combination of reducible oxides with nonprecious metals or spinel structures can also lead to CH 4 formation during the CO 2 hydrogenation. , In the synthesis of methanol, mainly Cu and Cu-Zn oxide based catalysts are employed . Producing long-chain hydrocarbons is also in the focus of research, typically employing tandem catalysts. In the EC CO 2 R, the most selective CO-producing catalysts are Au and Ag, while formic acid is mostly obtained on Sn-based materials. , Cu is unique in this sense, being the only metal capable of forming alcohols and hydrocarbons with reasonable rates. …”
Section: Introductionmentioning
confidence: 99%